2008
DOI: 10.1073/pnas.0707666105
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of glycosaminoglycan concentration in vivo by chemical exchange-dependent saturation transfer (gagCEST)

Abstract: Glycosaminogycans (GAGs) are involved in numerous vital functions in the human body. Mapping the GAG concentration in vivo is desirable for the diagnosis and monitoring of a number of diseases such as osteoarthritis, which affects millions of individuals. GAG loss in cartilage is typically an initiating event in osteoarthritis. Another widespread pathology related to GAG is intervertebral disk degeneration. Currently existing techniques for GAG monitoring, such as delayed gadolinium-enhanced MRI contrast (dGEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
658
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(678 citation statements)
references
References 35 publications
17
658
2
1
Order By: Relevance
“…Clinical studies examining the potential role of gagCEST in the assessment of OA-related cartilage degeneration are lacking. Feasibility studies using in vivo gagCEST have shown gagCEST MRI to be sensitive to GAG levels in the cartilage 20 . The value of this technique in assessment of OA-related cartilage degeneration needs further study.…”
Section: Rheumatologymentioning
confidence: 99%
“…Clinical studies examining the potential role of gagCEST in the assessment of OA-related cartilage degeneration are lacking. Feasibility studies using in vivo gagCEST have shown gagCEST MRI to be sensitive to GAG levels in the cartilage 20 . The value of this technique in assessment of OA-related cartilage degeneration needs further study.…”
Section: Rheumatologymentioning
confidence: 99%
“…APT MRI is a particular type of CEST MRI that specifically probes labile amide protons of endogenous mobile proteins and peptides in tissue [5,6]. In addition to APT MRI [5,6], useful CEST MRI contrast for clinical imaging can be generated from amine protons [7], hydroxyl protons [8], glycosaminoglycans [9], and glutamate [10], as well as from changes in creatine and lactate concentrations [11]. Glucose and iopamidol have been used as exogenous CEST agents that have been administered to patients [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…To this day there is no generally applicable direct GAG mapping technique available (Ling et al, 2008), despite the high GAG content in breast cancer tissue (Delehedde et al, 2001). Thus, for MRI study, we used 3D high-density cell cultures.…”
Section: Introductionmentioning
confidence: 99%
“…In breast pathogenesis quantitative changes in GAG may have important consequences on cells' proliferation and drug delivery (Eschenko et al, 2007). Considering the importance of GAG monitoring in small tissue samples (Ling et al, 2008) several techniques have been used to measure GAG content in vitro. These methods are based on high-performance liquid chromatography (HPLC) (Studelska et al, 2006), mass spectrometry (MS) (Harvey, 2006), electrophoresis (Jaffe, 1977), and immunofluorescence (Altman et al, 1993).…”
Section: Introductionmentioning
confidence: 99%